Using Rank-Frequency and Type-Token Statistics to Compare Morphological Typology in the Celtic Languages. Issue 2 (2nd April 2020) - Wilson, Andrew; Harvey, Rosie
ABSTRACT: Previous work has used Greenberg's synthetism index to compare three of the Celtic languages – Irish, Welsh, and Breton – but not the other three languages, namely Scottish Gaelic, Manx, and Cornish. This paper extends this earlier work by comparing all six Celtic languages, including two periods of Irish (Early Modern and Present Day). The analysis is based on a random sample of 210 parallel psalm texts (30 for each language). However, Greenberg's synthetism index is problematic because there are no operational standards for counting morphemes within words. We therefore apply a newer typological indicator (B7), which is based solely on lexical rank-frequency statistics. We also explore whether type-token counts alone can provide similar information. The B7 indicator shows that both varieties of Irish, together with Welsh and Cornish, tend more towards synthetism, whereas Manx tends more towards analytism. Breton and Scottish Gaelic do not show a clear tendency in either direction. Rankings using type-token statistics vary considerably and do not tell the same story.